Join IDNLearn.com to access a wealth of knowledge and get your questions answered by experts. Our community provides accurate and timely answers to help you understand and solve any issue.
Sagot :
Sure, let's solve the problem step by step.
### Part A: Complete the Square to Rewrite the Equation in Standard Form
Given the equation:
[tex]\[ x^2 + 4x + y^2 - 6y = -4 \][/tex]
We need to complete the square for both [tex]\( x \)[/tex]-terms and [tex]\( y \)[/tex]-terms.
#### Step 1: Completing the Square for the [tex]\( x \)[/tex]-Terms
The expression involving [tex]\( x \)[/tex] is [tex]\( x^2 + 4x \)[/tex].
1. Take half of the coefficient of [tex]\( x \)[/tex] (which is 4), and square it:
[tex]\[ \left( \frac{4}{2} \right)^2 = 2^2 = 4 \][/tex]
2. Add and then subtract this square inside the equation:
[tex]\[ x^2 + 4x = (x^2 + 4x + 4) - 4 = (x + 2)^2 - 4 \][/tex]
#### Step 2: Completing the Square for the [tex]\( y \)[/tex]-Terms
The expression involving [tex]\( y \)[/tex] is [tex]\( y^2 - 6y \)[/tex].
1. Take half of the coefficient of [tex]\( y \)[/tex] (which is -6), and square it:
[tex]\[ \left( \frac{-6}{2} \right)^2 = (-3)^2 = 9 \][/tex]
2. Add and then subtract this square inside the equation:
[tex]\[ y^2 - 6y = (y^2 - 6y + 9) - 9 = (y - 3)^2 - 9 \][/tex]
#### Step 3: Rewriting the Original Equation
Now, substitute the completed squares back into the equation:
[tex]\[ x^2 + 4x + y^2 - 6y = -4 \][/tex]
[tex]\[ (x + 2)^2 - 4 + (y - 3)^2 - 9 = -4 \][/tex]
Combine like terms:
[tex]\[ (x + 2)^2 + (y - 3)^2 - 13 = -4 \][/tex]
Add 13 to both sides to get the equation in standard form:
[tex]\[ (x + 2)^2 + (y - 3)^2 = 9 \][/tex]
This is the standard form of a circle equation:
[tex]\[ (x - h)^2 + (y - k)^2 = r^2 \][/tex]
### Part B: Identify the Center and Radius of the Circle
From the standard form equation [tex]\( (x + 2)^2 + (y - 3)^2 = 9 \)[/tex]:
1. The center [tex]\((h, k)\)[/tex] of the circle is found by looking at the transformations:
- [tex]\( (x + 2) \)[/tex] indicates a horizontal shift of -2
- [tex]\( (y - 3) \)[/tex] indicates a vertical shift of 3
Thus, the center is:
[tex]\[ (h, k) = (-2, 3) \][/tex]
2. The radius [tex]\( r \)[/tex]:
- The equation [tex]\( (x + 2)^2 + (y - 3)^2 = 9 \)[/tex] has [tex]\( r^2 = 9 \)[/tex]
- Therefore, the radius is:
[tex]\[ r = \sqrt{9} = 3 \][/tex]
So, the center of the circle is [tex]\((-2, 3)\)[/tex] and the radius is [tex]\(3\)[/tex].
### Part A: Complete the Square to Rewrite the Equation in Standard Form
Given the equation:
[tex]\[ x^2 + 4x + y^2 - 6y = -4 \][/tex]
We need to complete the square for both [tex]\( x \)[/tex]-terms and [tex]\( y \)[/tex]-terms.
#### Step 1: Completing the Square for the [tex]\( x \)[/tex]-Terms
The expression involving [tex]\( x \)[/tex] is [tex]\( x^2 + 4x \)[/tex].
1. Take half of the coefficient of [tex]\( x \)[/tex] (which is 4), and square it:
[tex]\[ \left( \frac{4}{2} \right)^2 = 2^2 = 4 \][/tex]
2. Add and then subtract this square inside the equation:
[tex]\[ x^2 + 4x = (x^2 + 4x + 4) - 4 = (x + 2)^2 - 4 \][/tex]
#### Step 2: Completing the Square for the [tex]\( y \)[/tex]-Terms
The expression involving [tex]\( y \)[/tex] is [tex]\( y^2 - 6y \)[/tex].
1. Take half of the coefficient of [tex]\( y \)[/tex] (which is -6), and square it:
[tex]\[ \left( \frac{-6}{2} \right)^2 = (-3)^2 = 9 \][/tex]
2. Add and then subtract this square inside the equation:
[tex]\[ y^2 - 6y = (y^2 - 6y + 9) - 9 = (y - 3)^2 - 9 \][/tex]
#### Step 3: Rewriting the Original Equation
Now, substitute the completed squares back into the equation:
[tex]\[ x^2 + 4x + y^2 - 6y = -4 \][/tex]
[tex]\[ (x + 2)^2 - 4 + (y - 3)^2 - 9 = -4 \][/tex]
Combine like terms:
[tex]\[ (x + 2)^2 + (y - 3)^2 - 13 = -4 \][/tex]
Add 13 to both sides to get the equation in standard form:
[tex]\[ (x + 2)^2 + (y - 3)^2 = 9 \][/tex]
This is the standard form of a circle equation:
[tex]\[ (x - h)^2 + (y - k)^2 = r^2 \][/tex]
### Part B: Identify the Center and Radius of the Circle
From the standard form equation [tex]\( (x + 2)^2 + (y - 3)^2 = 9 \)[/tex]:
1. The center [tex]\((h, k)\)[/tex] of the circle is found by looking at the transformations:
- [tex]\( (x + 2) \)[/tex] indicates a horizontal shift of -2
- [tex]\( (y - 3) \)[/tex] indicates a vertical shift of 3
Thus, the center is:
[tex]\[ (h, k) = (-2, 3) \][/tex]
2. The radius [tex]\( r \)[/tex]:
- The equation [tex]\( (x + 2)^2 + (y - 3)^2 = 9 \)[/tex] has [tex]\( r^2 = 9 \)[/tex]
- Therefore, the radius is:
[tex]\[ r = \sqrt{9} = 3 \][/tex]
So, the center of the circle is [tex]\((-2, 3)\)[/tex] and the radius is [tex]\(3\)[/tex].
We appreciate your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. IDNLearn.com has the solutions to your questions. Thanks for stopping by, and see you next time for more reliable information.